Identification of a novel mild isolate of areca palm necrotic spindle-spot virus (ANSSVm) lacking two cysteine proteases (HC-Pro1 and HC-Pro2) - Tan, Hang; Cao, Xianmei; Wang, Hongxing; Zhao, Ruibai; Huang, Xi (Frontiers in Microbiology, 2025)
Areca palm necrotic spindle-spot virus (ANSSV) encodes two tandem cysteine proteases, HC-Pro1 and HC-Pro2, at its N-terminal region, essential for maintaining viral infectivity. Deletion of either protease from an infectious clone abolishes infectivity. We report a mild ANSSV isolate, designated ANSSVm, from areca palm leaves exhibiting mild chlorosis. ANSSVm has a truncated genome of 7,868 nt, lacking both HC-Pro1 and HC-Pro2. An infectious ANSSVm clone established systemic infection in Nicotiana benthamiana through agroinfiltration but caused no symptoms in inoculated plants. Nucleotide polymorphisms in ANSSVm clones influenced infectivity, and residue variations of coat protein (CP) and P3 were identified as critical for intercellular movement. However, amino acid substitutions in ANSSVm CP did not alter its interactions with host proteins associated with viral movement. Further research is needed to uncover host factors and interactions essential for the systemic spread of potyvirids, presenting opportunities for targeted viral control strategies in plants.